1
$\begingroup$

Problem Statement:-

Consider a differentiable function $f:\mathbb{R}\rightarrow\mathbb{R}$ for which $f(1)=6$ and $$f(x+y)=3^x\cdot f(y)+9^y\cdot f(x),\;\;\forall x,y\in \mathbb{R}$$ then find $f(x)$.

My attempt:-

As the function is differentiable hence, we can differentiate the function w.r.t $x$ and $y$ but since $x$ and $y$ are independent, so $\dfrac{dy}{dx}$, so we get

$$f'(x+y)=3^x\ln3\cdot f(y)+9^y\cdot f'(x)\tag{1}$$

From the functional equation given in the problem we have

$$f(0+0)=3^0\ln{3}\cdot f(0)+9^0\cdot f(0)\implies f(0)=0$$

$$\therefore (1)\implies f'(y)=\ln{3}f(y)+c\cdot 9^y\tag{where $c=f'(0)$}$$

I am pretty much stuck after this.

If possible can you also tell me the line of thought that I should have while solving these types of problems.

$\endgroup$
1
  • $\begingroup$ Your last line is solving the equation is just a differential equation $y' = y + c9^t$, which can be solved with the standard methods. $\endgroup$
    – Mark
    Mar 15, 2017 at 2:13

1 Answer 1

3
$\begingroup$

I just happened to come up with an answer that doesn't need any differentiation.

We are given $$f(x+y)=3^x\cdot f(y)+9^y\cdot f(x)$$

On interchanging $x$ and $y$, we get

$$f(y+x)=3^y\cdot f(x)+ 9^x\cdot f(y)$$

we get $$3^x\cdot f(y)+9^y\cdot f(x)=3^y\cdot f(x)+ 9^x\cdot f(y)\\ \implies f(y)\cdot (3^x-9^x)=f(x)\cdot (3^y-9^y)\\ \implies \dfrac{f(x)}{3^x-9^x}=\dfrac{f(y)}{3^y-9^y}=k(\text{say})$$

So, we get $$f(x)=k({3^x-9^x})$$ Since $f(1)=6$, so $$f(1)=k(-6)=6\implies k=-1$$

$$\therefore \boxed{f(x)=9^x-3^x}$$

I don't know whether there are some other functions that satisfy the given conditions, if there are then please do post that in your answer.

And if you have some other approach please do post so that there is something new to learn.

$\endgroup$
0

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.